2013
DOI: 10.1007/s12010-013-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Reduction of Alkyl-3-oxobutanoates by Candida parapsilosis ATCC 7330: Insights into Solvent and Substrate Optimisation of the Biocatalytic Reaction

Abstract: Asymmetric reduction of alkyl-3-oxobutanoates mediated by Candida parapsilosis ATCC 7330 resulted in optically pure alkyl-3-hydroxybutanoates in good yields (up to 72%) and excellent enantiomeric excess (up to >99 %). A detailed and systematic optimisation study was necessary and was carried out to avoid the undesired transesterification reaction during the course of asymmetric reduction. Under optimised conditions, the (S)-alkyl hydroxyesters were produced predominantly except for the methyl ester which forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Even though cells harvested at 14 h produced the same ketone at less conversion (38%), these cells were used to visualise the site of biotransformation. For several other substrates reported earlier from our lab, the 14 h harvested cells produced the desired optically pure products with maximum ee (up to >99%) 1 2 3 6 7 26 29 30 33 34 35 .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Even though cells harvested at 14 h produced the same ketone at less conversion (38%), these cells were used to visualise the site of biotransformation. For several other substrates reported earlier from our lab, the 14 h harvested cells produced the desired optically pure products with maximum ee (up to >99%) 1 2 3 6 7 26 29 30 33 34 35 .…”
Section: Resultsmentioning
confidence: 69%
“…Earlier reports from our lab have shown that C. parapsilosis ATCC 7330 mediated the asymmetric reduction 1 2 3 27 and deracemisation 4 28 29 30 of aromatic/aliphatic prochiral ketones and secondary alcohols respectively. It seemed logical to use a prochiral ketone for the biocatalytic reduction which shows structural similarity to 1a for the study.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Microbial reduction of the carbonyl group is a convenient method for obtaining enantiomerically enriched β-hydroxyesters [3], which encouraged us to use a yeast strain in the biotransformation of α-acetylbutyrolactone. Whole-cell biocatalysts, in comparison to isolated enzymes, exhibit increased stability due to the protective cell matrix and are more profitable due to lower production costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…19 Several chemical reagents have been used to selectively oxidize secondary alcohols in the presence of primary alcohols, but they are not enantioselective. [24][25][26][27][28] Mechanistically, the deracemization using C. parapsilosis ATCC 7330 proceeds via stereo-inversion, i.e., enantioselective oxidation followed by reduction [a keto intermediate was observed using high-performance liquid chromatography (HPLC)]. HXN-200 for 3-O-benzylglycerol, phenyl-1,2-ethanediol, p-chlorophenyl-1,2-ethanediol and p-methylphenyl-1,2-ethanediol.…”
Section: Introductionmentioning
confidence: 99%